The influence of the Polish Financial Supervision Authority on the Bank's Management Board - Beata Grodziska-Modzelewska (The Central European Review of Economics and Management (CEREM), 2021)
Aim: The aim of the article is to analyze the supervisory measures available to the Polish Financial Supervision Authority in relation to the management board of banks operating in Poland and to indicate whether these measures have a real impact on their functioning and internal structure. On this basis, the proposed changes for the Polish supervision model will be indicated. The article is to be the basis for a discussion on the actual possibilities of supervisory authorities in individual European countries. Design/ Research methods: dogmatic and legal method, reflection on the Polish banking law, Polish and foreign legal literature. Conclusions/findings: The analysis of the indicated subject matter led to the conclusion that the possibility of using measures of an imperative nature is an element included in the concept of the Polish Financial Supervision Authority as a public administration body. Despite the powers vested in it, each time there must always be premises for the supervisory authority to apply certain sanctions to members of the bank's management board. Therefore, the Polish Financial Supervision Authority is not fully independent. Originality/ value of the article: The article is of value for legislative bodies, it indicates de lege ferenda postulates that should be applied for the Polish Financial Supervision Authority to be independent in the field of supervision over bank management boards. Implications of the research: The changes to the Polish banking law are necessary for the Polish Financial Supervision Authority to be able to exercise actual supervision, especially within the banking segment.
Keywords: K; K2; K23; 330; Polish Financial Supervision Authority; Public Administration Body; bank body; The bank's management board; resources ad rem; ad personam measures